Superalloys 718, 625, 706 and Various Derivatives (2005) 2005
DOI: 10.7449/2005/superalloys_2005_351_362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of δ-Phase on the Weldability and the Hot Ductility of Alloy 718

Abstract: In the weld repair cycles of alloy 718 the solution temperature is usually selected low enough to avoid grain growth in wrought material. At such low temperatures, however, δ-phase also precipitates and the amount increases with each repair cycle.It is well understood that the overall ductility is reduced by the presence of the δ-phase in alloy 718 and, as such, may reduce the weldability. But it is also reported that the δ-phase may cause incipient melting in grain boundaries at the heat affected zone, HAZ, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They identified rapid weld temperature variation and resultant conversion of γ′ and γ″ phases to δ phase as factors responsible for the decreased mechanical properties of the weld. It was found that after multiple long-term exposures to high-temperature cycles, IN718 welds degrade and become difficult to repair by welding because of the accumulation of Nb-rich δ phase in grain boundaries and the depletion of δ phase in adjacent intergranular regions in the IN718 microstructure [14,15]. Mary and Jahazi found that the loss of the δ phase in IN718 weld joint facilitates dynamic recrystallisation and dynamic recovery of γ grains in the weld joint during LFW [16].…”
Section: Introductionmentioning
confidence: 99%
“…They identified rapid weld temperature variation and resultant conversion of γ′ and γ″ phases to δ phase as factors responsible for the decreased mechanical properties of the weld. It was found that after multiple long-term exposures to high-temperature cycles, IN718 welds degrade and become difficult to repair by welding because of the accumulation of Nb-rich δ phase in grain boundaries and the depletion of δ phase in adjacent intergranular regions in the IN718 microstructure [14,15]. Mary and Jahazi found that the loss of the δ phase in IN718 weld joint facilitates dynamic recrystallisation and dynamic recovery of γ grains in the weld joint during LFW [16].…”
Section: Introductionmentioning
confidence: 99%